Sampling strategies to estimate suspended sediment concentration for turbidimeter calibration - Leandro Dalbianco; Rafael Ramon; Claudia A. P. de Barros; Jean P. G. Minella; Gustavo H. Merten; Elizeu J. Didoné (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The influx of sediments carried by rivers can be measured continuously using a turbidimeter through the indirect relationship between turbidity and suspended sediment concentration (SSC). However, this process is dependent on obtaining water samples with suspended sediments to calibrate the turbidimeter. Sampling can be carried out through different methods, resulting in errors and uncertainties in estimating the SSC. Four different possibilities for the composition of the calibration curve were tested in order to evaluate the effectiveness of the turbidimeter calibration for different sampling strategies. The study was conducted in 2012 and 2013 in two catchments in southern Brazil that had a strong sediment yield impact. The results indicate that sampling during rainfall events generate a significant and representative SSC for the turbidimeter calibration. The use of an integrating sampler for synthetic samples provides an effective calibration, but overestimates SSC compared to calibration from rainfall event sampling. The samples collected at fixed intervals - weekly and daily - generated an insufficient amount of data and are not representative of real sediment concentrations of the catchments.